Regional specificity of Algerian olive oil - H. Ghernoug; I. M. Chernukha; D. A. Utyanov (Пищевые системы)
Algeria is the ninth biggest producer of olive oil in the world and the fourth biggest producer of table olives. In 2023, 868,754 tons of this product were produced there. The paper examines the regional and climatic special features of olive oil (OO) production with detalization by this product grown in Algeria. The fatty acid composition of OO produced in various regions of the country was studied in comparison with oil from Spain and Italy. The positive effect of diets and medicines based on OO is described. The prospects of the development of target products based on protein-fat modules with the use of OO from certain Algerian regions are indicated.